SUSTAINABILITY DEVELOPMENT IN THE BUSINESS COMMUNITY STUDENTS OF UNIVERSITAS DUTA BANGSA SURAKARTA WITH UNI-KL MALAYSIA STUDENTS BUSINESS COMMUNITY - Indra Hastuti; Shariana Usman; Erna Chotidjah; Ratini Ratini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Sustainable development in the field of entrepreneurship in the business community, students need to be developed so that after graduating students can still run their businesses to develop and sustainably. Indonesian and Malaysian students after graduating from college on average look for work and do not continue their business. This research was conducted to obtain a model of developing entrepreneurship training through a Project Based Learning approach based on contextual business problems, applying a real planned business. make a profit, create jobs, reduce unemployment and poverty in Indonesia. This study uses a qualitative research method with a simulation observation research strategy. Observations were made on business groups, where each group consisted of 4-5 students from Duta Bangsa University and Malaysian University students. This research was conducted for 4 months divided into 2 stages. The first stage of the research is to identify and map the fields of Micro, Small and Medium Enterprises (MSMEs) with the prerequisites of entrepreneurial competence possessed by students, this stage is carried out using a qualitative descriptive method. The second stage is to build an entrepreneurship training development model based on a business plan with a Project Based Learning approach. The results of the research are mapping student entrepreneurship and obtaining an entrepreneurship training development model.